Analisa Cemaran Timbal Pada Lipstik Cair Menggunakan Spektrofotometri Serapan Atom (SSA) - Asiska Permata Dewi; Sri Kartini; Deri Islami (JURNAL FARMASI DAN MAKANAN, 2019)
Lipstick is the familiar product for women in difference age. Kind of lipstick that interested now is liquid lipstick. Not only it is cheap but also it can durable on lips. The actually using lipstick have to see of that safety from dangerous content like weight metal that content more than regulation. The objective of this research to know polluted metal content on some liquid lipsticks brand that they donâ€™t registered in BPOM RI. Determine of standard metal on samples used spectrometry atom absorption (SSA) on facet 283.22 nm. The average metal content on sample a was 0.45999 PPM, sample B was 2.96333 ppm, and sample C was 0.62334 ppm. It can conclude that liquid lisptics have polluted on weight metal content but its content still fulfill of BPOM Standard is 20 Âµg/grs or 20 mgs/L